A Novel Variant in the HINT1 Gene in a Girl with Autosomal Recessive Axonal Neuropathy with Neuromyotonia: Thorough Neurological Examination Gives the Clue - Rauchenzauner, Markus; Frühwirth, Martin; Hecht, Martin; Kofler, Markus; Witsch-Baumgartner, Martina; Fauth, Christine (Neuropediatrics, 2016)
We report a girl with autosomal recessive axonal neuropathy with neuromyotonia (ARAN-NM) who presented with asymmetric gait impairment, foot drop, and action myotonia on fast handgrip. Electrophysiological studies showed symmetrical axonal motor greater than sensory neuropathy, and neuromyotonic discharges on needle electromyography. ARAN-NM was confirmed by molecular genetic testing, which revealed a novel homozygous missense variant c.100G > A [p.(Glu34Lys)] in HINT1. This case shows that the diagnosis of ARAN-NM, as a new entity, has to be considered in the differential diagnosis of polyneuropathy in combination with neuromyotonia/action myotonia in children, even with asymmetric clinical presentation.
Keywords: HINT1; ARAN-NM; myotonia; neuropathy; children